COMMUNITY MEDIA MANAGEMENT FOR CULTURAL RESILIENCE: A CASE STUDY OF GALUH PRAMBANAN TV - Fiteer , Wahyudin; Prasetyo Jati, Rocky (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2021)
The purpose of this study is to ascertain how Galuh Prambanan TV manages its media community when introducing the Karawitan program. A qualitative descriptive method was taken in this investigation. The object of this research is the Galuh Prambanan TV media community which uses the channel from the Youtube application as the primary media. Data collection techniques are interviews, observation, and documentation—the validity of the data using source triangulation. In presenting the results, the researcher uses the concept of management, which consists of planning, organizing, directing, and supervising. From the study results, the researchers concluded that the program planning of the community media was going well. This was indicated by realizing the initial goals by implementing service goals to the community or community. In the concept of an organization, the manager has also established an effective and efficient work division to facilitate production and collaboration between teams in broadcasting content. Stages are also designated through producers' efforts from the media community in building motivation and creating communities to build motivation and create effective communities. The evaluation process carried out routinely by media managers and those in charge of content shows that the stages of supervision have also been carried out.